Differences in anthropometric characteristics between junior handball and volleyball players - Masanovic, B.; Vukasevic, V. (Journal of Anthropology of Sport and Physical Education, 2020)
The purpose of this study was to describe anthropometric characteristics of junior handball and volleyball players from the Serbian National League as well as to make a comparison between them. 61 male athletes were enrolled in this study, divided into three groups: 15 handball players, 14 volleyball players and 32 healthy sedentary subjects. The variables sample included 20 anthropometric measures that defined longitudinal and transversal dimensionality of skeleton, volume and mass of the body, and subcutaneous adipose tissue. The descriptive statistics were expressed as a mean (SD) for each variable, while the ANOVA and the LSD Post Hoc tests were carried out to detect differences between group. The results showed that a significant difference was found in variables body height, body weight, elbow diameter, thigh skinfold, calf skinfold, but no significant difference was found in the remaining 15 variables. Therefore, these findings may give coaches from the region better working knowledge and suggest to them to follow recent selection process methods and to be more careful during the process of talent identification.